Creation of Ultrasonic Equipment for Strengthening and Relaxation Treatment of Welded Structures in Railcar Building - Prykhodko, V.I.; Vysokolyan, M.V.; Volochai, V.V.; Prokopenko, G.І.; Mordyuk, B.N.; Cherepin, V.Т.; Krasovskiy, Т.А.; Popova, Т.V. (Science and Innovation, 2024)
A new modification of portable ultrasonic equipment (0.8 kW power, digitally controlled) has been developed for strengthening and relaxation treatment of metallic product surface. A batch of such devices has been produced; the design documents on the ultrasonic generator and impact instrument with a piezoceramic transducer have been prepared. Preparation of ultrasonic impact treatment technique for welded structures has been accomplished. The comparative tests related to the effects of different types of treatment and applied materials of welded structures on fatigue life have showed the expediency of ultrasonic impact treatment for the prolongation of operation life of products.